Review and analysis of the most common methods for shaping worm coils - Akramova Komila Shuxrat qizi (Zien Journals, 2022)
The operational qualities of a worm gear largely depend on the chemical composition, microstructure and properties of the materials used in the manufacture of the worm pair, as well as on the method of shaping the turns of the worms
Keywords: Worm; worm pair; cylindrical linear worm; non-linear worm